Innovation factors toward enhancing organisation performance : a study on the Malaysian healthcare sector - Nalini Subramaniam (2018)
Healthcare sector one of the key economic driver and crucial sector in nation Gross Domestic Product (GDP) contribution. Healthcare sector in Malaysia consists with three main industries, Pharmaceutical, Medical device and Biotechnology. Malaysian government had segregates lumps of funds to evolve the healthcare industry in transition towards innovation economy by 2020. Currently Malaysian obtained capable infrastructure such as manufacturing plant and in house Research and Development (R&D). However, healthcare industry slow in modification and innovates business model which leads the healthcare industry left behind compare to other developing countries such as China and India. Moreover, most of major death caused in Malaysia were chronic diseases. Malaysia forced to export generic medicines from foreign market and government spend lump of funds on medicines and medical equipment export even on generic medicines. On the other side, Malaysia healthcare sector attract most of medical traveler with its traditional therapies and reasonable medical expenses. Malaysia have been as one of the medical hub in ASEAN countries, however the industry faces tough competition in terms of price and quality along with its neighbour countries. Recently a few scholar has has underlined factors that determined innovation in healthcare. However, there has limited empirical evidence proposing an innovation factors towards enhancing organization performance of healthcare in Malaysian context. Therefore, more research needed to address the antecedents of innovation practice in order to boost up an organization performance in healthcare sector. Limited studies on innovation factors in healthcare sector in Malaysian context leads the path to researcher to overview on innovation factors which could boost the organization performance in terms of profit, sales, market share, and export rate, number of patents and global entry of the firm. Hence, Healthcare industry have capability to increase innovation to the next level and simultaneously enhance the contribution of gross domestic product and export activity. This study have identifies top management support, market orientation and research and development (R&D) alliance as an innovation factors which tested over organization performance of the healthcare industry. This study has attempted to analyze the innovation activities in healthcare industry in order to understand the factors leading to innovation towards enhancing organization performance. A research model has been developed and empirically tested through survey with 330 companies as a sample size. This study obtained data from 95 companies and were analyzed through logistics and multiple regression using SPSS. The result of this study indicated top management support as a most significant factor which influence organization performance in the context of healthcare industry in Malaysia.